Antiprotozoal Activity Profiling of Approved Drugs: A Starting Point toward Drug Repositioning - Kaiser, Marcel; Mäser, Pascal; Tadoori, Leela Pavan; Ioset, Jean-Robert; Brun, Reto (PLOS ONE, 2015)
Neglected tropical diseases cause significant morbidity and mortality and are a source of poverty in endemic countries. Only a few drugs are available to treat diseases such as leishmaniasis, Chagas’ disease, human African trypanosomiasis and malaria. Since drug development is lengthy and expensive, a drug repurposing strategy offers an attractive fast-track approach to speed up the process. A set of 100 registered drugs with drug repositioning potential for neglected diseases was assembled and tested in vitro against four protozoan parasites associated with the aforementioned diseases. Several drugs and drug classes showed in vitro activity in those screening assays. The results are critically reviewed and discussed in the perspective of a follow-up drug repositioning strategy where R&D has to be addressed with limited resources.